2022
DOI: 10.1086/711849
|View full text |Cite
|
Sign up to set email alerts
|

It’s Alive! Increasing Protective Action against the Coronavirus through Anthropomorphism and Construal

Abstract: It's Alive! Increasing Protective Action Against the Coronavirus Through Anthropomorphism and Construal News outlets often depict the coronavirus as a "burglar" or a "killer"-even though viruses are not technically alive. While imbuing this virus with human-like qualities may enable the public to feel as if they are better able to understand it, does anthropomorphizing the coronavirus lead people to adopt protective behaviors against the spread of the disease? Integrating construal level theory, we argue that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Anthropomorphism and future messages have a significant positive effect on consumer purchase intentions of bad food (Shao et al, 2020). Likewise, (Wan et al, 2020) suggests that the anthropomorphic message of coronavirus affects protective behavior.…”
Section: H2: Illustrating the Coronavirus With The Human Scheme (Corona Anthropomorphic) Increases Consumers' Fear Of The Effects Of The mentioning
confidence: 99%
See 3 more Smart Citations
“…Anthropomorphism and future messages have a significant positive effect on consumer purchase intentions of bad food (Shao et al, 2020). Likewise, (Wan et al, 2020) suggests that the anthropomorphic message of coronavirus affects protective behavior.…”
Section: H2: Illustrating the Coronavirus With The Human Scheme (Corona Anthropomorphic) Increases Consumers' Fear Of The Effects Of The mentioning
confidence: 99%
“…In this study, consumers will perceive the risk of anthropomorphic objects (anthropomorphic corona) being higher than objects (nonanthropomorphic) and then affect protective behavior. The study of (Wan et al, 2020) found that anthropomorphization of an agent, especially a negative agent, will make the agent appear more powerful and can affect how willing consumers are to act against this agent.…”
Section: H2: Illustrating the Coronavirus With The Human Scheme (Corona Anthropomorphic) Increases Consumers' Fear Of The Effects Of The mentioning
confidence: 99%
See 2 more Smart Citations
“…By anthropomorphizing the virus, the threat of illness is downplayed. Research has shown that anthropomorphizing diseases in health communication material increased people’s motivations to follow health recommendations (Wang et al, 2019 , Wang et al, 2020 ). In children’s literature, “the unfamiliar is anthropomorphized to make it familiar, comprehensible, and less worrisome” (Cox, 2017 , p. 22).…”
Section: Illustrations and Children’s Healthmentioning
confidence: 99%